ANALISIS PERKEMBANGAN EKONOMI WILAYAH DI INDONESIA - Mila Wardani; Puti Andiny; Rinaldi Syaputra (Smart Education, 2026)
Abstract: Regional development in the economic sector focuses on increasing productivity, measured through indicators such as population, income, employment opportunities, and value added from the manufacturing sector. Meanwhile, social development emphasizes gradual changes from underdeveloped to more advanced conditions in line with expected goals. The development paradigm should be directed toward a balance between equity, growth, and sustainability. Differences in economic contributions among regions in Indonesia indicate significant inequality. This is influenced by varying regional characteristics that affect economic growth in each area. Therefore, it is necessary to analyze regional economic development by considering 17 sectors of economic activity. This study applies several analytical methods, including economic growth rate (LPE), Theil Entropy Index to measure inequality, and shift-share analysis to examine structural economic changes. Furthermore, the MCDM-TOPSIS method is used to rank economic sectors as a basis for determining development priorities. The results of this analysis are expected to provide insights into leading sectors and those requiring improvement. The sector ranking can serve as input for the government in formulating national development policies, particularly in strengthening inter-sector linkages so that leading sectors can drive the growth of other sectors in a sustainable manner. Keywords: Ranking, MCDM, TOPSIS Abstrak: Pengembangan wilayah dalam bidang ekonomi berfokus pada peningkatan produktivitas yang diukur melalui indikator seperti jumlah penduduk, pendapatan, kesempatan kerja, dan nilai tambah sektor industri pengolahan. Sementara itu, pengembangan sosial menekankan perubahan bertahap dari kondisi kurang berkembang menuju maju sesuai harapan. Paradigma pembangunan perlu diarahkan pada keseimbangan antara pemerataan, pertumbuhan, dan keberlanjutan. Perbedaan kontribusi ekonomi antar wilayah di Indonesia menunjukkan adanya ketimpangan yang signifikan. Hal ini dipengaruhi oleh perbedaan karakteristik tiap wilayah yang berdampak pada pertumbuhan ekonominya. Oleh karena itu, diperlukan analisis perkembangan ekonomi wilayah dengan mempertimbangkan 17 sektor lapangan usaha. Penelitian ini menggunakan beberapa metode analisis, yaitu laju pertumbuhan ekonomi (LPE), Indeks Entropi Theil untuk mengukur ketimpangan, serta analisis shift-share untuk melihat pergeseran struktur ekonomi. Selanjutnya, metode MCDM-TOPSIS digunakan untuk melakukan perangkingan sektor lapangan usaha sebagai dasar penentuan prioritas pembangunan. Hasil analisis ini diharapkan dapat memberikan gambaran mengenai sektor unggulan dan sektor yang perlu ditingkatkan. Perangkingan sektor tersebut dapat menjadi masukan bagi pemerintah dalam merumuskan kebijakan pembangunan nasional, khususnya dalam memperkuat keterkaitan antar sektor sehingga sektor unggulan dapat mendorong pertumbuhan sektor lainnya secara berkelanjutan. Kata kunci: Perangkingan, MCDM, TOPSIS